2018
DOI: 10.3892/ijmm.2018.3783
|View full text |Cite
|
Sign up to set email alerts
|

Screening of circular RNAs and validation of circANKRD36 associated with inflammation in patients with type 2 diabetes mellitus

Abstract: Circular RNAs (circRNAs) are an abundant class of endogenous non-coding RNAs and are associated with numerous diseases, including cancer, cardiovascular diseases, and type 2 diabetes mellitus (T2DM). However, the association between circRNAs and inflammation or inflammatory cytokines in patients with T2DM remains to be fully elucidated. The purpose of the present study was to investigate the expression profiles of circRNAs in peripheral leucocytes of patients with T2DM and their association with inflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 30 publications
1
99
0
1
Order By: Relevance
“…We demonstrated that miR-22 was up-regulated by TGEV infection and had an anti-inflammation effect by targeting IL-6 and restraining DDX58, and CCL5, which is correlated with previous reports, but through different mechanisms. cir-cRNAs are an abundant class of endogenous ncRNAs and function as a regulator via various mechanisms such as miRNA sponge, binding to RNA-binding protein, and regulating transcription and translation of gene [44][45][46]. We found that miR-22 could be directly attached to ssc_circ_9380 and mediate TGEV-induced inflammation response, suggesting ssc_circ_9380 acts as the sponge of miR-22.…”
Section: Discussionmentioning
confidence: 89%
“…We demonstrated that miR-22 was up-regulated by TGEV infection and had an anti-inflammation effect by targeting IL-6 and restraining DDX58, and CCL5, which is correlated with previous reports, but through different mechanisms. cir-cRNAs are an abundant class of endogenous ncRNAs and function as a regulator via various mechanisms such as miRNA sponge, binding to RNA-binding protein, and regulating transcription and translation of gene [44][45][46]. We found that miR-22 could be directly attached to ssc_circ_9380 and mediate TGEV-induced inflammation response, suggesting ssc_circ_9380 acts as the sponge of miR-22.…”
Section: Discussionmentioning
confidence: 89%
“…A back-splicing event during the transcription process that ligates a splice donor site at the upstream to an acceptor sites at downstream of the RNA transcript, produces a covalently closed loop RNA product that does not contain either 5' to 3' polarity nor a poly-adenylated tail, and this is known as the circular RNA (circRNA) (Cao et al, 2018;Fang et al, 2018;Sulaiman et al, 2018;Hu et al, 2019). Due to its circular structure, circRNA is very stable and resistant to degradation by exoribonucleases (Liu et al, 2017;Cao et al, 2018).…”
Section: Circular Rnas (Circrnas)mentioning
confidence: 99%
“…Although circRNAs are known much earlier, its function and potential as biomarkers are not well understood. The most established function of circRNA is that circRNAs can act as a sponge to miRNAs to regulate gene expression (Cao et al, 2018;Fang et al, 2018;Hu et al, 2019), and in some cases, with proteins (Du et al, 2016). In terms of the circRNAs localization, some exonic circRNAs are abundantly present in the cytoplasm (Jeck et al, 2013), but no other information is available for other groups of circRNAs.…”
Section: Circular Rnas (Circrnas)mentioning
confidence: 99%
“…CircRNAs may have potential as biomarkers for the development of diabetes or as future molecular targets for novel diabetes therapeutics [14][15][16]. An important pre-requisite for this is the characterisation of circRNA sequences in diabetes-relevant tissues such as pancreatic islets and in more accessible tissues such as peripheral blood.…”
Section: Introductionmentioning
confidence: 99%